The effectiveness of leniency programs when firms choose the degree of collusion - Winand Emons (University of Bern, Department of Economics, 2018)
An antitrust authority deters collusion using fines and a leniency program. It chooses the probability of an investigation. Firms pick the degree of collusion: The more they collude, the higher are profits, but so is the probability of detection. Firms thus trade-off higher profits against higher expected fines. If firms are sufficiently patient, leniency is inffective; it may even increase collusion. Increasing the probability of an investigation at low levels does not increase deterrence. Increasing the probability of an investigation at high levels reduces collusion, yet never completely.
Keywords: D43; K21; K42; L40; 330; antitrust; cartels; deterrence; leniency